Daytime variations in glucose tolerance in people with impaired glucose tolerance - Santos, Maria Luiza dos; Aragon, Flávio F.; Padovani, Carlos R.; Pimenta, Walkyria P. (Elsevier, 2006)
To determine whether glucose tolerance varies throughout the day in people with impaired glucose tolerance (IGT). We studied 15 healthy IGT, and 18 matched normal glucose tolerant (NGT) individuals. Blood samples were taken every 30-120 min during a 24 h period in which all individuals had three mixed meals and nocturnal sleep. We measured glucose, free fatty acids, specific insulin, intact proinsulin, cortisol and growth hormone. Variable responses were considered as concentrations and areas under the curves. Comparison between the groups was by Student's t-test, Mann-Whitney, and analysis of variance. Higher total glucose response, inappropriate normal total insulin response, and unproportionally increased proinsulin total response were observed in the IGT group. Lower glucose tolerance occurred in IGT after dinner, as in the NGT, and after breakfast associated with increased insulin response after breakfast, and similar proinsulin response after all three meals. IGT had higher glucose response than NGT after breakfast and lunch, similar insulin responses, and increased proinsulin-insulin ratio after all three meals. Data from this study demonstrate that IGT individuals present lower glucose tolerance in the evening, as those with NGT, and in the morning, as reported in patients with type 2 diabetes. © 2006 Elsevier B.V. All rights reserved.
Keywords: 24 h Proinsulin response; Daytime glucose variations; Glucose tolerance; Impaired glucose tolerance; fatty acid; glucose; growth hormone; hydrocortisone; insulin; proinsulin; adult; analysis of variance; area under the curve; blood sampling; clinical article; comparative study; controlled study; fatty acid blood level; female; glucose blood level; glucose tolerance; growth hormone blood level; human; hydrocortisone blood level; impaired glucose tolerance; insulin blood level; insulin response; male; meal; night sleep; non insulin dependent diabetes mellitus; rank sum test; Student t test; Adult; Blood Glucose; Circadian Rhythm; Female; Humans; Insulin Resistance; Male; Middle Aged